Collegiate Sport Participation and Student-Athlete Development through the Lens of Emotional Intelligence - Lott, Gregory Harrison; Turner, Brian A (Journal of Amateur Sport, 2019)
A continued debate persists over the place of sport within institutions of higher education. Proponents of sport champion its ability to contribute to a holistic notion of education and develop an array of competencies touted in institutional missions. There is however a dearth of empirical data examining the educational impact of athletic participation at the college level. This paper assessed the educational ability of collegiate sport participation in a unique manner, through the lens of Emotional Intelligence (EI). Student-athletes and students at five NCAA Division III institutions completed online assessments prior to and after the completion of the winter sports seasons. Evidence was produced that participation in a single season of collegiate sport does not develop interpersonal, intrapersonal, and leadership capacities significantly differently from the collegiate experience of students not participating in athletics. Institutions are advised to explore EI interventions as way to maximize the educative potential of sport.